Some aspects of mutant p53 in ovarian cancer biology - Heublein, Sabine (Translational cancer research, 2016)
Epithelial ovarian cancer (EOC) is known as the most lethal gynaecologic malignancy. The poor prognosis of EOC has been attributed to e.g., late diagnosis of the disease and to chemoresistance. Further, we are still missing biomarkers that may reliably predict prognosis or chemosensitivity of an individual patient.